Tumor infiltrating lymphocytes after neoadjuvant IRX-2 immunotherapy in oral squamous cell carcinoma: Interim findings from the INSPIRE trial. (December 2020) - Wolf, Gregory T.; Liu, Siyu; Bellile, Emily; Sartor, Maureen; Rozek, Laura; Thomas, Dafydd; Nguyen, Ariane; Zarins, Katie; McHugh, Jonathan B.; Moyer, Jeff; Patel, Mihir; et al.
Highlights: Significant immune modulation was seen with neoadjuvant IRX-2 immunotherapy in this randomized, controlled clinical trial. Increases in CD8 positive tumor infiltrating lymphocytes were the most prominent changes. Greatest increases were seen in patients with p16 negative cancers. Abstract: Objectives: IRX-2 is a primary-cell-derived immune-restorative consisting of multiple human cytokines that act to overcome tumor-mediated immunosuppression and provide an in vivo tumor vaccination to increase tumor infiltrating lymphocytes (TILs). A randomized phase II trial was conducted of the IRX regimen 3 weeks prior to surgery consisting of an initial dose of cyclophosphamide followed by 10 days of regional perilymphatic IRX-2 cytokine injections and daily oral indomethacin, zinc and omeprazole (Regimen 1) compared to the identical regimen without IRX-2 cytokines (Regimen 2). Methods: A total of 96 patients with previously untreated, stage II-IV oral cavity SCC were randomized 2:1 to experimental (1) or control (2) regimens (64:32). Paired biopsy and resection specimens from 62 patients were available for creation of tissue microarray (n = 39), and multiplex immunohistology (n = 54). Increases in CD8+ TIL infiltrate scores of at least 10 cells/mm 2 were used to characterize immune responders (IR). Results: Regimen 1 was associated with significant increases in CD8+ infiltrates (p = 0.01) compared to Regimen 2. In p16 negative cancers (n = 26), significant increases in CD8+ and overall TILs were evident in Regimen 1 (p = 0.004, and 0.04 respectively). IRs were more frequent in Regimen 1 (74% vs 31%, p = 0.01). Multiplex immunohistology for PD-L1 expression confirmed an increase in PD-L1 H score for Regimen 1 compared to Regimen 2 (p = 0.11). Conclusions: The findings demonstrate significant increases in TILs after perilymphatic IRX-2 injections. Three quarters of patients showed significant immune responses to IRX-2. (NCT 02609386).